2005
DOI: 10.1308/003588405x51128
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes tumours of the breast – a retrospective study from 1982–2000 of 50 cases in Portsmouth

Abstract: Breast-conserving surgery is the treatment of choice for all benign lesions. For borderline and malignant lesions, excision with a wide margin reduces the rate of recurrence. If a diagnostic local excision biopsy or enucleation is performed, it should be followed by a definitive wider excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…Like others, we found the lungs to be most frequently involved, in keeping with the haematogenous route of spread [10]. Prognosis is extremely poor after the diagnosis of distant metastasis [10][11][12]. The only patient who had not died by the end of our study follow-up period had only been diagnosed a month prior; the rest had survived not more than 9 months after the diagnosis of distant metastasis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Like others, we found the lungs to be most frequently involved, in keeping with the haematogenous route of spread [10]. Prognosis is extremely poor after the diagnosis of distant metastasis [10][11][12]. The only patient who had not died by the end of our study follow-up period had only been diagnosed a month prior; the rest had survived not more than 9 months after the diagnosis of distant metastasis.…”
Section: Discussionsupporting
confidence: 86%
“…The significance of surgical margins is well reported [14,15], though some have also found no association between margin clearance and survival [16,17]. However, it is not known how wide a margin is necessary to minimise recurrence rates [12,18,19]. A 1cm margin clearance has been recommended [7,9], but this can be difficult to achieve even with a mastectomy as phyllodes tumours can present as very large masses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lungs and skeleton are the usual sites of distant metastasis for PT, almost all other organs have been shown to be afflicted, including the adrenal glands [17], brain [7, 9-11, 17, 18], gastrointestinal tract [17,[19][20][21], heart [22], kidney [23], liver [2,10,15,16,24,25], mesentery [26], pancreas and pleura [15], retroperitoneum [16], soft tissues [2,5,15,26,27], spleen and thyroid [19], tonsil [28], uterus [19], and vulva [29].…”
Section: Sites Of Metastasismentioning
confidence: 99%
“…Studies describing MRI signs performed on women with mild PBT found oval masses sometimes lobulated of regular contours, presenting a hyper-signal in T2 or hyper and iso-signal in T2 and hypo-signal in T1, raising itself quickly after injection of the contrast product (24,26 This study reported that the signs in favor of malignancy are: 1. Irregular contours, an hyper signal in T1 2.…”
mentioning
confidence: 69%